Learning to Plan–and Planning to Learn - and Michael, Donald N. (Miles River Press, 1997)
Don Michael says that, yes, the world can meet future social and organizational challenges - but only if we learn to plan in order– to live uncertainty– to learn from mistakes, actually embrace error– to do goal setting that is future-responsive– to lower barriers by spanning boundaries– to improve personal interaction– to overcome resistance to learning and change.This book treats planning as the way for persons, organizations, and societies to learn their way into the future. It reveals the complex and unavoidable social psychological resistances to learning that must be overcome by competent citizenry in order to plan for the future. A viable ecology, Third World development, new-city building, democratic government in a turbulent society – all depend on the anticipation of future conditions and on planning to meet these conditions.
Keywords: Social science